Croton restingae sp. nov. (Euphorbiaceae), a new species of section Adenophylli from the state of Rio de Janeiro, Brazil, and its phylogenetic relationships - Sodré, Rodolfo Carneiro; da Silva, Marcos José; Caruzo, Maria Beatriz Rossi; Riina, Ricarda (European Journal of Taxonomy, 2023)
We describe and illustrate Croton restingae Sodré & Riina sp. nov., a new species endemic to a restricted area in the state of Rio de Janeiro, Brazil, characterized by a particular type of vegetation of the Atlantic Forest known as restinga. The new species belongs to Croton sect. Adenophylli subsect. Laceratoglandulosus, which is supported by morphology and a phylogenetic analysis based on nrDNA ITS sequence data. Croton restingae is most closely related to C. echioides and C. laceratoglandulosus, also in subsect. Laceratoglandulosus, with which it shares the fruit columella with three non-inflated, flat or slightly ascending apical appendages. Croton restingae differs from them by its sessile or shortly stipitate leaf nectaries, revolute pistillate sepals, styles distally 2-fid and basally united forming a column, and larger capsules (7.5–8 × 8.5–9.3 mm). Croton restingaeʼs habitat, conservation status, phenology, morphology and phylogenetic relationships are discussed, and a map with its geographic distribution is also included.